Mobile Pervasive Augmented Reality Systems for Outdoor Environments Contexts - Pascoal, R.; de Almeida, A.; Sofia, Rute C. (PhD Forum Madness and Forum Posters, 2019)
This work debates on the aspects required to boost the acceptance and use of Mobile, Pervasive Augmented Reality Systems, and on the need to develop context-aware close-to-real-time feedback mechanisms that take into consideration a continuous measurement of Quality of Experience. For this purpose, the work introduces the requirements of users in outdoor environments contexts of this kind and delves on how these smart systems can be integrated into context-aware feedback systems achieving high Quality of Experience.